COMMUNITY READINESS ASSESSMENT FOR A COMMUNITY-BASED COLLECTING AND ARCHIVING PROJECT FOR CONTEMPORARY KOMIKS - Boquiren, Alain Andrew S. (Journal of Philippine Librarianship; Vol 38 (2018), 2019)
This study assessed the willingness and readiness of the local komiks community in the National Capital Region to collaborate in a community-based archiving initiative. The author also identified concerns of this community regarding the preservation of their works, namely: the protection of their rights as content creators, the protection of their works from piracy, and the sustainability of the preservation effort. A project plan based on the findings was developed to help komiks community members and archive practitioners collaborate on a collecting and archiving project, which can be used as a starting point for a komiks preservation practice.
Keywords: archiving; collecting project; comic books; community-based; komiks; Library and Information Studies; Philippine comics; preservation; National Capital Region